Pengaruh Pengetahuan dan Religiusitas Petani Terhadap Minat Membayar Zakat Pertanian Padi di Dusun Lelong Desa Lelong Kecamatan Praya Tengah Kabupaten Lombok Tengah: Pengaruh Pengetahuan dan Religiusitas Petani Terhadap Minat Membayar Zakat Pertanian Padi di Dusun Lelong Desa Lelong Kecamatan Praya Tengah Kabupaten Lombok Tengah - Selviatun, Huliya; Kartika Dewi, Resti (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, dan Publikasi, 2023)
This study aims to test the influence of farmers knowledge and farmer religiosity, on the interest in paying rice farming zakat in Lelong Hamlet, Lelong Village, Central Praya District, Central Lombok Regency. This study used a quantitative approach with associative type. The population in this study was 129 farmers in Lelong Hamlet, with data collection techniques using questionnaires and sample totaling 39 people. The data analysis methods used is multiple analysis tests. The results showed that simultaneously farmer knowledge and farmer religiosity had a positive effect on the interest in paying rice agricultural zakat. While partially, knowledge has no effect on the interest in paying rice agricultural zakat and the religiosity of farmers has a positive effect on the interest in paying rice agricultural zakat.